2020
DOI: 10.1071/ah18250
|View full text |Cite
|
Sign up to set email alerts
|

'…If I don't have that sort of money again, what happens?': adapting a qualitative model to conceptualise the consequences of out-of-pocket expenses for cancer patients in mixed health systems

Abstract: ObjectiveThe aim of this study was to explore Western Australian cancer patients’ experiences of out-of-pocket expenses (OOPE) during diagnosis and cancer treatment using a phenomenological approach. MethodsSemi-structured interviews were conducted with a purposive convenience sample of 40 Western Australian cancer patients diagnosed with breast, lung, prostate or colorectal cancer. Participants were asked about the impact of their diagnosis, the associated costs and their experience within the health system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 33 publications
1
21
1
Order By: Relevance
“…The response rate for the survey was lower than expected; however, the sample size was large enough to ascertain difference between participants, and 70% of participants commented on issues pertaining to costs. Factors identified by participants who provided open comments reflect the views of those who participated in the in-depth interviews 25 and not only confirmed our previous findings but also provided a better insight into the issue from multiple perspectives. A further limitation is that lung cancer patients were underrepresented.…”
Section: Strengths and Limitationssupporting
confidence: 84%
“…The response rate for the survey was lower than expected; however, the sample size was large enough to ascertain difference between participants, and 70% of participants commented on issues pertaining to costs. Factors identified by participants who provided open comments reflect the views of those who participated in the in-depth interviews 25 and not only confirmed our previous findings but also provided a better insight into the issue from multiple perspectives. A further limitation is that lung cancer patients were underrepresented.…”
Section: Strengths and Limitationssupporting
confidence: 84%
“…For rural patients this is magnified with substantial additional costs than those faced by urban patients, particularly for transportation, accommodation and relocation if required, and further compounded by excessive leave requirements, to attend appointments and surgeries 19,40,41 . There is a scarcity of information available as to the extent of rural financial hardship in people with CKD, and this requires further research, especially to assess the impact the financial hardship exerts on decision making and access to all forms of treatment 42 .…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 39 , 40 There is a scarcity of information available as to the extent of rural financial hardship in people with CKD, and this requires further research, especially to evaluate the impact the financial hardship exerts on decision-making and access to all forms of treatment. 41 …”
Section: Discussionmentioning
confidence: 99%
“…Regret about decision to have surgery (Hardcastle et al, 2018;Parker et al, 2014) Forced self-management strategies (Hardcastle et al, 2018;Kwok et al, 2015) Upset and disturbance (Player et al, 2014;Rowlands et al, 2015) Shock (Bolton & Isaacs, 2018) Feelings of unpreparedness and isolation (Chambers et al, 2018) Anxiety and uncertainty (Kwok & White, 2014) Forced to learn by 'hard knocks' (Moore et al, 2014) Exacerbation of side effect (Philp et al, 2017) Disappointment (Kwok et al, 2015) Lack of information about available services Prevented psychosocial service use (Gunn et al, 2013;Pascal et al, 2015) Intensified feelings of isolation (Pascal et al, 2015) Reliance on family members for language translation (Levesque, Gerges, Wu, & Girgis, 2020) Treatment nonadherence and stress (Slavova-Azmanova et al, 2019) Feelings of angst and frustration (McGrath et al, 2012) Lack of information about potential financial impact Unexpected financial burden (Moore et al, 2014;Newton et al, 2020) Vulnerable to making substantial financial decisions they may have later regretted (McGrath, 2017) Physical…”
Section: Poor Communication and Survivorship Planningmentioning
confidence: 99%
“…Negative impact on life (Philp et al, 2017;Rowlands et al, 2015) Financial burden, reduced confidence, reluctance to socialise (Bolton & Isaacs, 2018) Feelings of incapability at work, need for assistance to complete tasks, disconnection from family life (Player et al, 2014) Struggle with daily domestic activities (Brown et al, 2015) Challenges when socialising (Parker et al, 2014) Compromised work role upon return to work (Anderson et al, 2011) Fear of cancer recurrence and psychological distress Feelings of vulnerability, loneliness and abandonment (Pascal et al, 2015) Practical Financial and employment issues Financial burden (McGrath, 2017;McGrath et al, 2012;Parker et al, 2014) Need for government benefits (McGrath, 2017;Parker et al, 2014) Added stress (McGrath, 2016(McGrath, , 2017 Prevented psychosocial support (Gunn et al, 2013;Thomas et al, 2013) Inconvenience (Chambers et al, 2018) Treatment nonadherence (Newton et al, 2020) Loss of confidence and competence (McGrath et al, 2012) Difficulties accessing services Prevented asking for help (O'Callaghan et al, 2016) Added stress (Schiena et al, 2019) Feelings of isolation and worsened mental health (Gunn et al, 2013) Feelings of guilt and unworthiness (Parker et al, 2014) Emotional Lack of understanding and holistic care Feelings of being unsupported, mistrust and disempowerment (Williams et al, 2020) Feelings of distress and dissatisfaction, negative psychological impact (Thomas et al, 2013) Psychological Lack of psychological support Negative impacts on QoL (Moore et al, 2014) Feelings of fear, isolation and abandonment (Pascal et al, 2015) Social None reported None reported…”
Section: Consequences Of Cancer Treatmentsmentioning
confidence: 99%